The Use Of E-Muamalat Facilities In Attracting Customer Interest IN PT. Bank Muamalat Indonesia TBK. KCP Panyabungan - misbah misbah; budi gautama; muhammad wandisyah; samsuddin muhammad (Institut Agama Islam Negeri Padangsidimpuan, 2021)
Banking service facilities using information technology are called Electronic Muamalat. With advances in information technology, customers can make transactions from anywhere and anytime quickly and easily, so as to further increase the volume of transactions that occur at a bank. However, only some of the customers of Bank Muamalat Indonesia Tbk. KCP. Panyabungan that uses E-Muamalat. The purpose of this study is to find out how customers perceive E-Muamalat and the factors that cause customers to use E-Muamalat at PT. Bank Muamalat Indonesia Tbk. KCP Panyabungan. Theories used in this study include Definition of Interests, Banking Services, Technology Banking Services, Electronic Banking, Banking History, Types of Electronic Transactions and Products at PT. Bank Muamalat Indonesia Tbk. Panyabungan KCP. This research is field research using a qualitative approach with data collection techniques using the Interview, Documentation, Observation method, while the data sources used are primary and secondary. Based on the results of research that has been carried out by researchers, it can be seen that customer perceptions of E-Muamalat are very practical, super-fast, and accurate without having to come to the office when they want to transact, besides that the factors that cause customers to use E-Muamalat because they don't want to miss out on electronic-based banking products. Banking.